Online Ojek Drivers’ Cultural Perception on Complying with Traffic Regulations in Medan, Indonesia - Kesuma, Agung Kastria; Lubis, Lusiana Andriani; Nurbani, Nurbani (Technium Social Sciences Journal, 2021)
The objective of this research was to find out the cultural perceptions of online ojek (motorcycle taxi) drivers in complying with traffic regulations. The research used a qualitative method through in-depth interviews with six online ojek drivers and 2 customers who used the Grab and Gojek online applications in Medan. The data were analyzed by using the qualitative method. The result of the research showed that online ojek drivers had already known and understood the existing traffic regulations as the requirements for becoming drivers. The bad role of intercultural communication between online ojek drivers and their customers causes differences in cultural perceptions so that it opens up opportunities for not complying with traffic regulations.